2020
DOI: 10.1021/acsami.0c17544
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Electronic Interaction at the Atomic-Layer-Deposited MoS2 Monolayer/SiO2 Interface

Abstract: The electronic structure of an atomic-layer-deposited MoS 2 monolayer on SiO 2 was investigated using X-ray absorption spectroscopy (XAS) and synchrotron X-ray photoelectron spectroscopy (XPS). The angle-dependent evolution of the XAS spectra and the photon-energy-dependent evolution of the XPS spectra were analyzed in detail using an ab-initio electronic structure simulation. Although similar to the theoretical spectra of an ideal free-standing MoS 2 ML, the experimental spectra exhibit features that are dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Among the strategies proposed, one of them was to deposit a seed layer of S on SiO 2 to prevent the interaction between Mo and O on the surface, which causes the formation of the buffer layer (Figure 8a) as supposed to be an ideal MoS 2 layer (Figure 8b). However, as reported by Lee et al, 163 there may be parasitic conduction between S and O in a similar ideal free-standing MoS 2 layer as shown in Figure 8c,d.…”
Section: Metalsupporting
confidence: 68%
See 2 more Smart Citations
“…Among the strategies proposed, one of them was to deposit a seed layer of S on SiO 2 to prevent the interaction between Mo and O on the surface, which causes the formation of the buffer layer (Figure 8a) as supposed to be an ideal MoS 2 layer (Figure 8b). However, as reported by Lee et al, 163 there may be parasitic conduction between S and O in a similar ideal free-standing MoS 2 layer as shown in Figure 8c,d.…”
Section: Metalsupporting
confidence: 68%
“…The film is grown at 100 °C as opposed to the 300 °C deposition temperature by Tan et al 106 While amorphous, it can be annealed for crystallization. Recently, Lee et al 163 studied the electronic interaction at the interface between SiO 2 surface and MoS 2 deposited by ALD of Mo(CO) 6 and H 2 S. They found that even though SiO 2 is highly insulating, because of the orbital hybridization of the oxygen ions at the interface, the O 2p can contribute to valence as well as conduction bands. This causes a considerable electronic interaction between MoS 2 and SiO 2 .…”
Section: Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…Driven by this fact, various complex self-assembling structural morphologies of MoS 2 monolayer sheets by desulfurization appear. In previous studies, it was found that interesting self-assembling nanostructures can form because of the covalent binding of atropisomeric molecules onto the substrate, indicating the important role of the molecule–molecule and molecule–substrate interactions on self-assembling behaviors. ,,, Interestingly, the physical properties of MoS 2 monolayer sheets may be tuned by the substrates, for example, thermal conductivity and electronic properties. , Due to the different molecule–molecule and molecule–substrate interactions, different substrates may result in different self-assembling morphologies of 2D layered sheets. As is known, a single layer of MoS 2 is composed of S–Mo–S sandwiched structures, and each Mo atom is covalently bonded with six S atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Since ALD process characteristics are highly suitable for layer-by-layer growth with low-temperature thickness and uniformity control, many research groups have attempted to grow wafer-scale monolayer or few-layer MoS 2 films. However, none of these studies have been successful for formation of a complete monolayer of MoS 2 using ALD at the wafer scale. Due to steric hindrance and screening effects caused by the surface-adsorbed precursor, the amount of deposited material per one ALD cycle is often smaller than an atomic monolayer .…”
Section: Introductionmentioning
confidence: 99%